THE EFFECT OF COMPENSATION, COMPETENCE, AND JOB PLACEMENT ON JOB SATISFACTION - Mada Anggana; Yohanes Susanto; Ronal Aprianto (LPPM UNIVERSITAS BINA INSAN, 2025)
This study aims to investigate the influence of competency and job placement on the job satisfaction of Non-Civil Servant Government Employees (PPNPN) at Silampari Airport Lubuklinggau, with compensation as a moderating variable. Using a quantitative approach, the research employed a survey method with a saturated sample of 134 respondents. Data collection was carried out through questionnaires, and the analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that compensation has the strongest positive effect on job satisfaction, followed by competency, which also demonstrates a positive and significant impact. However, job placement does not significantly influence job satisfaction. Moreover, compensation does not act as a moderating variable that enhances or weakens the relationship between competency and job placement on job satisfaction. These findings emphasize the critical role of fair and transparent compensation systems and the need for continuous competency development, such as through training programs, to increase job satisfaction among PPNPN employees. The study underlines the necessity for organizations, particularly public institutions like airports, to prioritize employee welfare through effective human resource management practices. The research provides valuable insights and recommendations for policymakers to develop more strategic and welfare-oriented HR policies that can improve the performance and satisfaction of non-civil servant personnel in government sectors